Kepemimpinan Berpusat Pada Pembelajar Di Era Digital Dan Efikasi Guru: Peran Mediasi Pembelajaran Profesional Guru - ., Suriyanto; Handayani, Ririn; Abdillah, M. Rasyid (CV. ITTC INDONESIA, 2025)
The research was conducted on teachers at SMP 18 Pekanbaru, SMP 12 Pekanbaru, SMPN 3 Pekanbaru, and SMPN 6 Pekanbaru with the aim of examining the role of professional learning in mediating the effect of learner-centered leadership on teacher self-efficacy. The study population consisted of 178 individuals. Based on this population size, according to the Krejcie and Morgan table (1970), the sample size for this study was 123 individuals. The sampling method employed in this research was Systematic Random Sampling. All respondents were used to obtain primary data related to the variables, which were collected through a questionnaire using a 5-point Likert scale. All data obtained were analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. The study found that learner-centered leadership had a significant positive effect on teacher self-efficacy; learner-centered leadership had a significant positive effect on professional learning; professional learning had a significant positive effect on teacher self-efficacy; and professional learning mediated the effect of learner-centered leadership on teacher self-efficacy.